2020
DOI: 10.3390/plants9081023
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Mineral and Phenolic Profiles and Their Association with the Antioxidant, Cytotoxic Effect, and Antimicrobial Potential of Lycium chinense Miller

Abstract: This study aimed at investigating the Lycium chinense Miller leaf extract mineral and phenolic compound profiles as well as antioxidant and antimicrobial potential. We determined the leaf extract mineral composition, identified its major mineral components, and quantified secondary metabolites. We also measured the leaf extract antioxidant potential and found that it varies in a concentration-dependent manner. We observed a significant and higher positive correlation between DPPH and ABTS assays compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 69 publications
(80 reference statements)
2
5
0
Order By: Relevance
“…For example, higher rutin, chlorogenic acid, and luteolin concentrations significantly reduced the growth of NIH/3T3 cells. Similarly, there was a strong positive correlation between cytotoxicity and the concentration of protocatechuic acid, chlorogenic acid, p-coumaric acid, salicylic acid, quercetin, luteolin, and quercetin derivatives [80][81][82][83]. Here, we observed a strong positive correlation between cytotoxicity and p-coumaric acid, salicylic acid, chlorogenic acid, salicylic acid, and rutin contents, suggesting that the higher concentration of these compounds is associated with the cytotoxicity effect of A. japonica.…”
Section: Discussionsupporting
confidence: 66%
“…For example, higher rutin, chlorogenic acid, and luteolin concentrations significantly reduced the growth of NIH/3T3 cells. Similarly, there was a strong positive correlation between cytotoxicity and the concentration of protocatechuic acid, chlorogenic acid, p-coumaric acid, salicylic acid, quercetin, luteolin, and quercetin derivatives [80][81][82][83]. Here, we observed a strong positive correlation between cytotoxicity and p-coumaric acid, salicylic acid, chlorogenic acid, salicylic acid, and rutin contents, suggesting that the higher concentration of these compounds is associated with the cytotoxicity effect of A. japonica.…”
Section: Discussionsupporting
confidence: 66%
“…Phenolic compounds have antioxidant capacities in EVOO since they can eliminate peroxyl and alkoxy radicals and chelate transition metal ions present in traces ( Visioli et al, 1998 ). Several elements are known for their antioxidant properties ( Perna et al, 2012 ; Thiruvengadam et al, 2020 ). Indeed, in the present study ( Supplementary Table S8 ), significant correlations were observed between the antioxidant activity and elements.…”
Section: Resultsmentioning
confidence: 99%
“…Due to their specific and rapid response when changes in the environment occur, phenolic compounds have been proved to be suitable biomarkers or early warnings [ 9 , 10 , 11 , 12 ]. These compounds are specialized metabolites that benefit the bearing organism through several biological properties (e.g., antioxidant capacity) [ 13 ]. Interest in this field has been growing, given the potential medical contributions of such phenolic compounds to human health and personal care: immunostimulant and antitumoral drugs or products for skin aging [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%